PERTUMBUHAN DAN PERKEMBANGAN TANAMAN SAMAMA (Anthocephalus macrophyllus) DALAM WAKTU X TAHUN DI DESA HATUSUA KECAMATAN KAIRATU KABUPATEN SERAM BAGIAN BARAT - Parinussa, Ingrid; Siahaya, Ludia; Talaohu, Moda (PT. BARRINGTONIA ASIATICA LESTARI, 2024)
The aim of this research is to determine the increase in diameter and increase in height of Samama plants (Anthocephalus macrophyllus) for one year after 10 years of measuring the relationship between soil pH and soil moisture with the growth rate of Samama plants (Anthocephalus macrophyllus) as well as environmental factors that influence the growth of Samama. This research uses a stepwise method by calculating the average annual increase (MAI), current annual increase (CAI), and multiple regression analysis. The results of further research showed that there was an increase in the diameter of the Samama plant (Anthocephalus marcophyllus) from 9 years to 10 years. It is known that the Current Annual Increase (CAI) of the tenth diameter is 1.0 (cm/plant/yr). And the average annual increment (MAI) in diameter is 2.82 (cm/plant/yr), the current annual increment (CAI) is high, namely 1.11 (cm/plant/yr) and the average annual increment (MAI) is high namely 2.74 (cm/plant/yr).